KETEPATAN DAN KEPATUHAN KONSUMSI DIIT DIABETES MELLITUS PENDERITA RAWAT INAP DI RSU BRAYAT MINULYA SURAKARTA - Jeannette Mila H C; Muchammad . Sulchan (Jurnal Kesehatan Masyarakat Indonesia, 2003)
Background: The main basis for the therapy of Diabetes mellitus (DM) is the regulation of the diet that full fills the energy needs of the patient. in theory, to determine the total energy needs, first one has to determine the nutritional state of the patient by calculating the Relative Body weight of the patient. In reality, doctor often determines the diet only based on an estimation of the patient's body weight Several .factors influence the patients' obedience to the die, among others the taste of food, food habits, and their knowledge of the illness. This examination concerned the Accuracy of as well as the obedience to DM diet of the patient in Brayat Minulya General Hospital in Surakarta. The aim of this examination was to get to know the degree of accuracy of the obedience to the consumption of DM diet of patients in Brayat Minulya General Hospital in Surakarta. Method: The accuracy of DM diet was evaluated by comparing the total calorie value af the nutritional state of patients. The obedience of the patients was evaluated by measuring the average of the leftovers during three days, expressed in per cents. The taste of food, food habitats, and patients' knowledge af DM were evaluated by way of scoring the patients' answers to the questionnaire. The results obtain C show that 88, 9% of the diets prescribed by the doctors were not accurate as to the total calorie value, whereas 8 I, 5% of the patients obeyed the diet given. The result of the evaluations of the factors influencing the obedience of the patients to the diet showed that Bl,5%found that the food was tqstefull,82,5% had food habits in accordance with the food served to them in the hospital, and 74, l% of the patients had a good knowledge of DM. There is a correlation between the taste of food, food habits, and the patients' knowledge of DM on one side and their obedience to the DM diet on the other side. Conclusion: a great number of DM diets prescribed by the doctors are not accurate as to the total calorie value. A great number of patients obey the diet. The more tasteful the diet, the more in accordance with food habits of the patients, and the better their knowledge of diabetes mellitus, the better the patients obits the diet. Keywords: DM, diet, accurate, obedience